Radiative properties of 'Eu'in Li–Al–Si–O ceramics: Effect of 'Si' to 'Li' ratio. Issue 1 (1st January 2022) - Mohapatra, M.; Vinothkumar, P.; Sathyamoorthy, K.; Murugasen, Priya
Abstract: Four Li–Al–Si– O -based ceramic compounds with varying Si to Li ratios were synthesized via a high-temperature reaction route and characterized by X-Ray diffraction, scanning electron microscopy, and photoluminescence techniques. Eu was used as an activator in these four compositions namely, LiAlSiO4, LiAlSi2 O6, LiAlSi3 O8, and LiAlSi4 O10, and the radiative properties were evaluated. The activator concentration was optimized in all these samples to 2 mol%. The photoluminescence emission intensity and decay time values increased with the Si to Li ratio. The relative intensities of the emission spectra and the lifetime values indicated that the rare earth ion stabilizes itself at interstitial positions in the lattice having approximately C2v symmetry. The chromaticity indices for the four ceramic samples doped with Eu were calculated that showed near red emission for all. To get an idea about their commercial utility, color purity, quantum efficiencies for the phosphors were evaluated. The emission profile of the prepared samples was compared with a commercial sample. The Judd-Ofelt parameters, transition probabilities, branching ratios, and quantum efficiencies were also calculated for these systems. It was observed that the metal-ligand bond covalency decreased with an increase in the Si to Li ratio which was responsible for the increase in the emission intensities and luminescence decay time values.